Impatience and uncertainty: experimental decisions predict adolescents' field behavior - Sutter, Matthias; Kocher, Martin; Glätzle-Rützler, Daniela; Trautmann, Stefan T. (Working papers in economics and statistics, 2010)
We study risk attitudes, ambiguity attitudes, and time preferences of 661 children and adolescents, aged ten to eighteen years, in an incentivized experiment. We relate experimental choices to field behavior. Experimental measures of impatience are found to be significant redictors of health related field behavior and saving decisions. In particular, more impatient children and adolescents are more likely to spend money on alcohol and cigarettes, have a higher body mass index (BMI) and are less likely to save money. Experimental measures for risk and ambiguity attitudes are only weak predictors of field behavior. -- experiments with children and adolescents ; risk ; ambiguity ; time preferences ; health status ; savings ; external validity ; field behavior
Keywords: Arbeitspapier; Graue Literatur; Feldforschung; Ambiguität; Risiko; Heranwachsender